Assessing the â€œGotong-royongâ€ Spirit in the Merdeka Curriculum: A Case Study of Studentâ€™s Engagement in Renewable Energy Project-Based Learning (PjBL) - Iin Nashihah; Elvin Yusliana E; Dewanto Harjunowibowo (Postgraduate, University of Mataram, 2023)
This research is conducted to find out the Gotong Royong attitude toward the students in Merdeka Curriculum. The method of this research is quantitative method. The purpose of this research is to describe the attitude of Gotong Royong which was obtained by the students during learning activity. The research was conducted in February 2023. The place of this research was SMA Al Azhar Syifa Budi Solo. The population was X I IPA 1. The school was selected based on the driving schools with supporting teachers as organizer teachers in Merdeka Curriculum. There are 3 steps in this research such as preparation, design, and implementation. There the observation of 4 aspects during the learning process. These aspects are related to the development of the Gotong Royong dimension from the Pancasila Student Profile in the Merdeka Curriculum. The result of Gotong Royong's attitude obtains a very good category. This category is observed in the students during the learning process with the highest score being 4 and the lowest score is 1. Gotong Royong's attitude is based on the good category (3 aspects) and the good category (1 aspect). Although Gotong Royong's attitude is based on the highest presentation to all of the scores in the collaboration dimension. Score 1 is 42%, score 2 is 43%, score 3 is 85%, and score 4 is 38%.